The Correlation Between Using Instagram and Body Image at Sman 7 Pekanbaru - Fitry Erlin; Eka Malfasari; Nadya Muharanu Putri (Risenologi, 2022)
Instagram is a social media that focuses on sharing photos that are widely used by teenagers in interpreting their self-image. Posting photos wants others to see that they are a perfect figure with an ideal body shape and a dream for every teenager. The purpose of this study was to determine the correlation between the use of Instagram on body image in adolescents. This research was quantitative research with a correlation design that employed cross-sectional. The analysis used univariate and bivariate analysis using chi-square. The study was conducted from May 2018 at SMAN 7 Pekanbaru with a total of 153 teenagers as respondents. The results conclude that there is no correlation between the use of Instagram on body image seen from the p-value of 0.962 (> 0.05). With this research, it is hoped that the correlation between Instagram use and adolescent body image will be used as input for coaching and as a reference for further research.